Media Pembelajaran Gaya Mengajar Komando Untuk Guru PJOK - Ahmat Fauzi; Advendi Kristiyandaru; Abdul Rachman Syam Tausikal (Smart Education, 2021)
The purpose of this article is to find out how the commando teaching style instructional media for corner teachers. Specifically, the teacher must have the ability to develop learning strategies and be able to choose the right strategy in learning activities. Teaching style is one of the abilities that can support the teacher's ability in the learning process. Command teaching style is one of 11 teaching styles in Muska Mosston's book. The commando teaching style was the first to be introduced among the other styles, and is most often used by corner teachers. However, the teaching style of command in its implementation is not only commanding, but also there are several steps that must be fulfilled as explained by Muska Mosston. Learning media is an intermediary that can help teachers to better understand the commando teaching style.